The Relationships Between Sewing and Forward Head Posture - Diky Krisnanda Sugianto; Safun Rahmanto; Dimas Sondang Irawan (Physical Therapy Journal of Indonesia, 2020)
Introduction: The working attitude that is often done by human beings in doing work among others standing, sitting, bent, squat, walking, and others. Attitudes such as work are done hanging from the condition of the system’s existing work. Forward head posture is the incident common much going on in modern times. It is described as a gesture of brought the heads of forward from the middle part of the shoulder. Head of moving forward, so the center of gravity shifted. To compensate this shift in the center of gravity, drift the upper body backward and shoulders slipped to future that head gets a move into the anterior than vertebrae. Every activity daily life needs a posture certain to be maintained. Any deviation from the normal pattern posture affecting the joints and muscle, so as to cause the pathological condition. An imbalance in the muscles causing shortening of fiber or lengthening next leads to changes in posture. This research aims to understand the relationship that activity sew against forwarding head posture (FHP) at a tailor.Methods: This study using design cross-sectional involving 30 respondents using purposive sampling. The data from respondents carried out using a quick check the exposure (QEC) and then in test measurements forward head posture. We analyzed the data by chi-square.Results: The statistics conducted by the SPSS-24 test using chi-square showed significantly (P value= 0,018). Where if the signs have been less than 0.05 so that h1 is accepted and h0 is rejected. Conclusion: There is a correlation that activity sew against forwarding head posture on a the tailors.